Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Contribution of SNP arrays in diagnosis of deletion 2p11.2-p12. - Rocca, Maria Santa; Fabretto, Antonella; Faletra, Flavio; Carlet, Ombretta; Skabar, Aldo; Gasparini, Paolo; Pecile, Vanna (Gene, 2012)
Deletions of the short arm of chromosome 2 are exceedingly rare, having been reported in few patients. Furthermore most cases with deletion in 2p11.2-p12 have been studied using standard karyotype and so it is not possible to delineate the precise size of deletions. Here, we describe a 9-year-old girl with a 9.4 Mb de novo interstitial deletion of region 2p11.2-p12 identified by SNP array analysis. The deleted region encompasses over 40 known genes, including LRRTM1, CTNNA2 and REEP1, haploinsufficiency of which could explain some clinical features of this patient such as mental retardation, speech delay and gait abnormalities. A comparison of our case with previously reported patients who present deletions in 2p11.2-p12 was carried out. Our case adds new information to the deletion of 2p11.2-p12, improving the knowledge on this rearrangement.
Keywords: Abnormalities, Multiple; Child; Chromosomes, Human, Pair 2; Female; Humans; Intellectual Disability; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sequence Deletion

De novo 6.9 Mb interstitial deletion on chromosome 4q31.1-q32.1 in a girl with severe speech delay and dysmorphic features. - Fabretto, Antonella; Santa Rocca, Maria; Perrone, Maria Dolores; Skabar, Aldo; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Deletion of the terminal part of long arm of chromosome 4 is a condition characterized by facial dysmorphisms, cardiac and limb defects, and developmental delay. Deletions usually involve the terminal part of the chromosome and most frequently are interstitial. Here, we report a de novo interstitial deletion resulting in a microdeletion of 6.9 Mb involving 4q31.3-q32.1 segment, detected by SNPs-Array technique in a 4-year-old female showing severe speech delay, mild facial dysmorphisms, and joint laxity. Phenotype-genotype relationships looking at the genes involved in this part of the chromosome were also carried out and data compared with those previously described.
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 4; Developmental Disabilities; Female; Genotype; Humans; Language Development Disorders; Phenotype; Sequence Deletion

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A new case of duplication of the MDS region identified by high-density SNP arrays and a review of the literature. - Faletra, Flavio; Devescovi, Raffaella; Pecile, Vanna; Fabretto, Antonella; Carrozzi, Marco; Gasparini, Paolo (J Appl Genet, 2011)
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Child; Female; Gene Duplication; Humans; Microtubule-Associated Proteins; Myelodysplastic Syndromes; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prognosis

A case of lymphedema-distichiasis syndrome carrying a new de novo frameshift FOXC2 mutation. - Fabretto, Antonella; Shardlow, Alison; Faletra, Flavio; Lepore, Loredana; Hladnik, Uros; Gasparini, Paolo (Ophthalmic Genet, 2010)
PURPOSE: Lymphedema-Distichiasis (LD, OMIM 153400) is an autosomal dominant disorder with variable expression. The mutated gene implicated is FOXC2, which encodes for a forkhead transcription factor involved in the development of the lymphatic and vascular system. LD is characterized by late childhood or pubertal onset lymphedema of the limbs and distichiasis. Other associations have been reported, including congenital heart disease, ptosis, scoliosis. CONCLUSIONS: Here we describe a case of LD carrying a de novo frameshift mutation of FOXC2 who presented a prepubertal onset of lower limbs lymphedema and mild distichiasis associated with other anomalies such as webbing neck and ptosis.
Keywords: Abnormalities, Multiple; Adolescent; Eye Abnormalities; Eyelashes; Face; Forkhead Transcription Factors; Frameshift Mutation; Humans; Lymphedema; Male; Syndrome

Two cases of Noonan syndrome with severe respiratory and gastroenteral involvement and the SOS1 mutation F623I. - Fabretto, Antonella; Kutsche, Kerstin; Harmsen, May-Britt; Demarini, Sergio; Gasparini, Paolo; Fertz, Maria Cristina; Zenker, Martin (Eur J Med Genet, 2010)
Noonan syndrome (NS) is an autosomal dominant, inherited disorder characterized by facial dysmorphism, congenital heart defects, and reduced postnatal growth. Dysregulated RAS-MAPK signalling is the common molecular basis for NS, a genetically heterogeneous disease. Germline mutations in genes encoding small GTPases of the RAS family (KRAS and NRAS), modulators of RAS function (PTPN11, SOS1 and SHOC2) or downstream signal transducers (RAF1) are causative for NS. SOS1 is the second major gene for NS after PTPN11. Compared to patients with mutations in other genes, SOS1 mutation-positive individuals in general tend to have a more favorable outcome, with less short stature and cognitive impairment. We describe two unrelated patients with NS carrying the same heterozygous SOS1 missense mutation (c.1867T > A/p.F623I). The phenotype of both patients is remarkable as they show uncommon clinical features such as pulmonary lymphangiectasis, congenital pleural effusions, severe feeding problems, and laryngomalacia. These findings may be related to the specific mutation present in our two patients, or be part of the SOS1 phenotype. Detailed clinical assessment of large cohorts of patients with NS and SOS1 mutation is required to clarify this initial observation.
Keywords: Child, Preschool; Genes, ras; Germ-Line Mutation; Heterozygote; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Noonan Syndrome; Phenotype; SOS1 Protein